2019
DOI: 10.1177/0300060519863520
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural damage of normal-appearing white matter in subcortical ischemic vascular dementia is associated with Montreal Cognitive Assessment scores

Abstract: ObjectivesThis study was performed to determine whether multimodal biomarkers are more strongly associated with the Montreal Cognitive Assessment (MoCA) scores compared with the Mini-Mental State Examination (MMSE) scores, and whether they are correlated with the Clinical Dementia Rating (CDR) in patients with subcortical ischemic vascular dementia (SIVD).MethodsPatients diagnosed with SIVD were enrolled. Peripheral blood hypersensitive C-reactive protein, white matter lesion volume (WMLV), fractional anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Our study showed no significant differences in total MoCA score or MoCA subscores between patients who differed in stroke location (right vs. left) or etiology (cerebral hemorrhage vs. cerebral infarction). Similarly, we found that the total MoCA score was not associated with patients' age, sex, or education level at the onset of basal ganglia stroke, in contrast to previous studies [21]. Our failure to detect an association between sex and cognitive subscores may be attributed to our small sample.…”
Section: Discussioncontrasting
confidence: 92%
“…Our study showed no significant differences in total MoCA score or MoCA subscores between patients who differed in stroke location (right vs. left) or etiology (cerebral hemorrhage vs. cerebral infarction). Similarly, we found that the total MoCA score was not associated with patients' age, sex, or education level at the onset of basal ganglia stroke, in contrast to previous studies [21]. Our failure to detect an association between sex and cognitive subscores may be attributed to our small sample.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, disruption of structural connectivity has been detected even in cognitively normal cSVD patients, affecting mainly the prefrontal areas, whereas in MCI cSVD patients, networks from frontal and parietal regions were disrupted 103 . Interestingly, MD and FA were more strongly associated with MoCA than MMSE scores, suggesting that the former might be more useful as a cognitive screening tool for cSVD patients 93,104,105 . However, the T2 relaxation time of the NAWM in cSVD patients was associated with cognition, which the DTI metric of the NAWM failed to achieve 106 …”
Section: Resultsmentioning
confidence: 99%
“…103 Interestingly, MD and FA were more strongly associated with MoCA than MMSE scores, suggesting that the former might be more useful as a cognitive screening tool for cSVD patients. 93,104,105 However, the T2 relaxation time of the NAWM in cSVD patients was associated with cognition, which the DTI metric of the NAWM failed to achieve. 106 Global FA, MD, PSMD, structural network measures, and ROI analysis were performed in a group of cSVD patients (from no cognitive impairment to MCI) and healthy controls to evaluate cognition.…”
Section: Complications and Outcomes Of Csvd Associated With Dti-deriv...mentioning
confidence: 99%
“…Since the pathogenesis and pathological basis of vascular dementia are relatively special, most patients often have different underlying cerebrovascular diseases, and ischemic stroke is the most common. 4,5 The risk of cerebrovascular lesions increases substantially in the elderly population due to the reduced metabolic capacity of peripheral circulation and vascular smooth muscle motor regulation. Once cerebrovascular lesions occur, blood circulation is often impaired, and the local brain tissue is continuously undersupplied with blood and oxygen.…”
Section: Introductionmentioning
confidence: 99%